Dengue algorithms integrated into the IMCI guidelines: an updated assessment in five Southeast-Asian countries - Petzold, Stephanie; Rosenberger, Kerstin; Wills, Bridget; Deen, Jacqueline; Weber, Martin W.; Jänisch, Thomas (PLoS neglected tropical diseases, 2022)
Dengue is not included explicitly in the WHO Integrated Management of Childhood Illness (IMCI) algorithm. However, the assessment, classification and management of dengue has been incorporated into several IMCI country adaptations. We aimed to evaluate the dengue algorithms incorporated into IMCI guidelines and discuss the need for harmonization, including an extension of the age range for IMCI.